A catalytic independent function of the deubiquitinating enzyme USP14 regulates hippocampal synaptic short‐term plasticity and vesicle number. (2nd January 2014) - Walters, Brandon J.; Hallengren, Jada J.; Theile, Christopher S.; Ploegh, Hidde L.; Wilson, Scott M.; Dobrunz, Lynn E.
<x xml:space="preserve">Abstract</x> Key points Mice carrying the ataxia (axJ) mutation have a 95% reduction in the deubiquitinating enzyme USP14, which results in a reduction in hippocampal paired pulse facilitation, a form of short‐term synaptic plasticity. Hippocampal synapses in axJ mice have a 50% reduction in synaptic vesicles but no change in the initial release probability, which is a novel mechanism for regulating paired pulse facilitation. USP14 modulates hippocampal short‐term plasticity and structure independent of its deubiquitinating activity, as overexpression of a catalytically inactive form of USP14 restores hippocampal paired pulse facilitation and vesicle number to the ataxia mice. Pharmacological inhibition of the proteasome also rescues the deficits in hippocampal short‐term plasticity in ataxia mice, implying that the loss of USP14 causes increased protein degradation. These results suggest that USP14 plays a modulatory role in regulating protein turnover by the proteasome that is independent of its canonical role in the disassembly of polyubiquitin conjugates. Abstract The ubiquitin proteasome system is required for the rapid and precise control of protein abundance that is essential for synaptic function. USP14 is a proteasome‐bound deubiquitinating enzyme that recycles ubiquitin and regulates synaptic short‐term synaptic plasticity. We previously reported that loss of USP14 in axJ mice causes a deficit in paired pulse facilitation (PPF) at hippocampal synapses. Here we report that USP14 regulates synaptic function through a novel, deubiquitination‐independent mechanism. Although PPF is usually inversely related to release probability, USP14 deficiency impairs PPF without altering basal release probability. Instead, the loss of USP14 causes a large reduction in the number of synaptic vesicles. Over‐expression of a catalytically inactive form of USP14 rescues the PPF deficit and restores synaptic vesicle number, indicating that USP14 regulates presynaptic structure and function independently of its role in deubiquitination. Finally, the PPF deficit caused by loss of USP14 can be rescued by pharmacological inhibition of proteasome activity, suggesting that inappropriate protein degradation underlies the PPF impairment. Overall, we demonstrate a novel, deubiquitination‐independent function for USP14 in influencing synaptic architecture and plasticity.